Neonatal intestinal colonization with extended-spectrum β-lactamase–producing Enterobacteriaceae—a 5-year follow-up study. (September 2018) - Nordberg, V.; Jonsson, K.; Giske, C.G.; Iversen, A.; Aspevall, O.; Jonsson, B.; Camporeale, A.; Norman, M.; Navér, L.
Abstract: Objectives: To analyse Klebsiella pneumoniae (KP) isolates from an outbreak of extended-spectrum β-lactamase (ESBL)-producing KP and Escherichia coli (EC) among infants admitted to neonatal intensive care units and to determine the duration of the intestinal colonization. Methods: We performed a prospective cohort study of intestinal ESBL-KP/ESBL-EC colonized neonates after a 5-month outbreak in two neonatal intensive care units. Whole genome sequencing, multilocus sequence typing, core genome multilocus sequence typing, pulsed-field electrophoresis and PCR for bl aCTX-M were performed on the first isolates. Stool cultures were performed every second month after discharge until 2 years after discharge and at 5 years of age. The last positive samples were analysed with pulsed-field gel electrophoresis and PCR for bl aCTX-M . The intestinal relative dominance of ESBL-producing Enterobacteriaceae was determined. Results: Thirteen of 17 patients colonized with ESBL-KP/ESBL-EC survived. Isolates from 16 of 17 patients were available for analysis and featured the same strain type of ESBL-KP: sequence type 101. The strain had capsule type K29 and harboured bla CTX-M-15 . The virulence genes irp1, irp2, iutA, kfu and mrk were detected in all isolates. The median length of colonization was 12.5 months (range, 5–68 months). After 2 years, two of 13 patients were carriers of ESBL-KP and one of 13 of ESBL-EC. At 5 years of age, one neonate was colonized with ESBL-EC. No infant experienced an ESBL-KP/EC-infection during follow-up. Conclusions: Two years after discharge, almost one fourth of the study participants were ESBL/KP-EC carriers. ESBL-KP sequence type 101 persisted in two of 13 children for 23 to 26 months. One patient was colonized with ESBL-EC at age 5 years.